MYTHOLOGICAL TRANSFORMATION IN MODERN INDONESIAN NOVELS - Nurgiyantoro, Burhan; Anwar Efendi; Maman Suryaman; Anis Maslihatin (Universitas Negeri Yogyakarta, 2024)
In the factuality, there are many fictional works that raise myth elements and use as reference in writing. Literary works inevitably exist in communities that have cultures and this is well acknowledged by writers who eventually receive them actively-productively. The present study is aimed at identifying these matters in modern Indonesian literature including myth sources, author’s attitudes that are hypogrammed, and myth functions. The study is conducted on five novels produced in the 2000s. Various myth stories contain life values that can be used as inspirations and culturel references in the writing of modern Indonesian novels and, simultaneously, as allegories and metaphors of life in the present time. The novels are partly set as they are in the myth stories, while partly are transformed into the life background of the present time. Even though the novels are set in the time background of the myth stories, the personalities and life philosophy of the characters reflect the life situations of the present time. The writers’ attitudes towards myths are partly continuing and augmenting the myth conventions although through the transformations of plots and characters (myth of concern), and, on the contrary, partly freeing, deviating, and rebelling (myth of freedom). In the case of rebellion to the myth conventions (Roro Jonggrang), it seems that it is due to the influences of the feminist ideas that emphasize the importance of life equalities between men and women. Women need not be always defeated or dominated by men.